Pediatric surgery experiences of a tertiary referral hospital: International Classification of Diseases spectrum for teaching, planning, and scaling up services - Jain, Col Sunil; Chandra, Lt Col Naveen; Thapar, Col Rajeev Kumar (Indian Journal of Child Health, 2019)
Introduction: Pediatric surgery provides the opportunity to intervene positively in a wide array of diseases with potential lifelong impact. Objective: The objective of this study was to evaluate the significance of pediatric surgery under vast circumstances. Materials and Methods: All children in the age group of 0–10 years operated in a tertiary care hospital were analyzed. Grouping of cases was done using the International Statistical Classification of Diseases and Related Health Problems 10th Revision (International Classification of Diseases [ICD]-10)-WHO Version (2016) and incorporating terminology from the ICD-11 Beta Draft. Results: “Developmental anomalies” accounted for 79.1% of cases, while 20.9% were “acquired conditions requiring surgical intervention.” The common congenital malformations were those of the genital organs (17%), followed by those of the digestive (13%) and nervous system (13%), urinary system (12%), circulatory system (8%), and cleft lip and palate (7%). The essential surgery package for congenital anomalies should include expertise in repair of cleft lip and palate, anomalies of genital, digestive, nervous, urinary, and musculoskeletal system. Referral to superspecialty center is required only for “congenital malformations of the circulatory system.” Conclusion: Majority of the workload (79.1%) due to “developmental anomalies” points toward need for skills in correcting these, restoring anatomy for the proper growth, and physiological functioning. Inclusion of indirect inguinal hernia in the Chapter 20 ‘Developmental anomalies’ (ICD-11) will contribute to correct international comparisons and guide planning.